2004
DOI: 10.1002/ana.20251
|View full text |Cite
|
Sign up to set email alerts
|

Novel PINK1 mutations in early‐onset parkinsonism

Abstract: PINK1 was recently found to be associated with PARK6 as the causative gene. We performed mutation analysis in eight inbred families whose haplotypes link to the PARK6 region. We identified six pathogenic mutations (R246X, H271Q, E417G, L347P, and Q239X/R492X) in six unrelated families. All sites of mutations were novel, suggesting that PINK1 may be the second most common causative gene next to parkin in parkinsonism with the recessive mode of inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 252 publications
(174 citation statements)
references
References 7 publications
5
165
1
2
Order By: Relevance
“…More than 50 mutations in the PINK1 gene (1p36), located at the PARK6 locus, have been identified in PD-affected patients [239][240][241][242][243] and these mutations are believed to account for up to 1-8 % of sporadic cases with early onset [244].…”
Section: Pink1 (Park6)mentioning
confidence: 99%
“…More than 50 mutations in the PINK1 gene (1p36), located at the PARK6 locus, have been identified in PD-affected patients [239][240][241][242][243] and these mutations are believed to account for up to 1-8 % of sporadic cases with early onset [244].…”
Section: Pink1 (Park6)mentioning
confidence: 99%
“…PINK1 mutants remain diffusely distributed and are not recruited to mitochondria, resulting in reduced mitochondrial elimination PD-associated mutations in PINK1 have been found in both the kinase and C-terminal domains [2,16]. Among these mutations, G309D, L347P, and G409V are expected to cause a reduction in the kinase activity of PINK1 [13,14,17].…”
Section: Mitochondrial Elimination Is Accomplished By Overexpression mentioning
confidence: 99%
“…More recent studies have suggested a role for this motif in kinase regulation (27), because variations within this loop appear to favor alternative modes of C-helix positioning (21,28). Mutations at this site produce severe (29,30) and/or dominant-negative effects (31).…”
Section: N-lobementioning
confidence: 99%